O silêncio da discórdia: uma perspectiva acerca da cumulação de ritos no cumprimento de sentença de alimentos, no âmbito das varas de família da comarca de Mossoró/RN - Barbosa, Rebeca Fernandes (Universidade Federal Rural do Semi-Árido, 2019)
The present study addressed issues related to the institute of compliance with the sentence of maintenance, highlighting the controversial debate about cumulation of rites of arrest and expropriation in the same process. It was investigated how they have handled these demands in the scope of Family Courts of the Comarca of Mossoró / RN, from the positions of the magistrates holding the jurisdictional units. It was analyzed the influence of the syncretic perspective of the civil process and its relation with the fulfillment of the sentence, in order to explore the peculiarities that involve the procedure provided for the satisfaction of the food credit. The research showed how legal provisions, doctrine and jurisprudence address the issue. After that, we proceeded to investigate how the cumulation of procedural rites has occurred at the local level, specifically in the Region of Mossoró / RN. The method of dialectic approach was used, and a bibliographical, documentary and information collection was carried out by means of an interview with the Judges of the Family Courts of the Comarca of Mossoró / RN. With the study, it was concluded that the syncretic view favors the understanding of the possibility of cumulative compliance with the sentences issued by the same executive title in the same process, although there is a relevant controversy about the practical applicability of the coexistence of the rites of arrest and expropriation in the execution of sentence of foods. This occurs in both doctrine and jurisprudence, and the interpretation of the Civil Procedure Code is not peaceful. At local level, it was found that the understanding of the magistrates of the Family Courts of the Comarca of Mossoró / RN is not unanimous. However, because of the content of Joint Ordinance No. 31/2017 TJRN, there is a consensus among the judges to unify the procedure in the normative terms of the State Court, in which there is guidance not to determine the separation for a separate assessment sentencing or execution of extrajudicial title meals involving the last three installments (recent food) and the oldest installments (past food). In this way, executive acts of personal coercion (civil imprisonment) and expropriation of property (attachment) must be carried out in the same process.
Monografia
Keywords: Alimentos; Cumulação; Cumprimento de sentença; Processo civil; Sincretismo processual; CIENCIAS SOCIAIS APLICADAS::DIREITO